Application of Response Surface Methodology (RSM) for Simultaneous Optimization of Kinetic Parameters Affecting Gold Leaching in Thiosulfate Based Media: A Statistical Approach - Nomsa P. Baloyi; Joseph M. Nseke; Mamookho E. Makhatha (Journal of Chemistry)
Over the years, the use of new alternative lixiviants for gold extraction has been investigated to overcome the environmental concerns resulting from the cyanidation process. Moreover, with global economic factors causing a decline in gold prices, it is crucial that novel hydrometallurgical methods of extracting gold minimise operational costs by using low-priced reagents such as thiosulfate. In the current study, the response surface methodology (RSM) approach is used to optimize the kinetic factors (temperature and copper, ammonia, and thiosulphate concentration) affecting gold leaching. Gold ore assayed at 16 g/t was characterized through X-ray fluorescence and X-ray diffraction spectrometric analysis as well as scanning electron microscope-energy dispersive spectrometric technique. Gold ore was predominantly siliceous with minor pyritic content. The results indicate a strong relationship between the actual gold leaching recovery data and the RSM model. Correlation coefficients R2 and adjusted R2 are equivalent to 0.9869 and 0.9817. Gold leaching in copper-ammonia-thiosulfate media is best described as a surface chemical reaction-controlled process, suggesting that gold dissolution in thiosulfate is considerably affected by the increase in temperature. The effect of temperature is mostly significant, contributing up to 64.65% of the gold recovery response model. The contribution percentages of the effects of time, thiosulfate [S2O3], ammonia [NH3], and copper [Cu] concentrations were calculated as 12.81%, 5.88%, 5.19%, and 4.65%, respectively. All investigated kinetic parameters were found statistically significant with pvalue <0.05. The optimal concentrations of gold leaching media to achieve potentially complete dissolution of gold from its ore in copper-ammoniacal thiosulphate media based on the effect of the investigated parameters were 0.5 M S2O3, 3 M NH3, and 0.003 M Cu2+ with a desirability value equivalent to unity (d = 1.000).